Economic Consequences Following The Absence Of Workers In Private Enterprises Due To Poor Physical Abilities Associated With Job Health (for Adolescent Workers In Lower Management) - Guelloula , Mohammed Djallal Eddine; Mehidi , Mohamed (sports creativity, 2025)
This study aimed at evaluating the level of physical fitness elements associated with job health of adolescent workers in private enterprises, and how that relates to absence from the job. The study also sought to determine the expenses paid and sustained by private enterprises because of their absent workers. To achieve this aim, the study utilized the descriptive method as it best suits the nature of the topic on a research sample of 36 adolescent workers. The method of research involved the workers going through a selected number of job-related physical fitness tests along with the processing of relevant statistics using the financial accounting system (FAS). The study found that there is indeed a correspondence between workers’ absence and deficiency in physical fitness associated with job health, which burdens private enterprises with additional costs that could diminish their profit margin or force upon them unexpected consequences.